The role of CEO regulatory focus in increasing or reducing corporate carbon emissions - Andreas Wagner; Denise Fischer-Kreer (Business Strategy and the Environment, 2023)
This article contributes to the emerging stream of corporate carbon emission research, which zooms in on CEOs' responsibility in organizations' strategic decision-making. This investigation offers new knowledge of how a CEO's regulatory focus can shape whether firms reduce their carbon footprints. Building on regulatory focus theory, this study proposes how the two distinct motivational dispositions (i.e., promotion or prevention focus) of a CEO relate to corporate carbon emissions. We empirically analyzed S&P 500 firms from 2007 to 2018. The findings indicate that CEOs with a high promotion focus are positively associated with corporate carbon emissions, whereas CEOs with a high prevention focus are negatively linked to corporate carbon emissions, with the latter relationship weakened by industry volatility. The findings reported in this study enrich carbon emission research by devoting attention to cognitive and motivational aspects of CEOs for corporate carbon management.
Keywords: 330; CEO characteristics; climate change; decarbonization; regulatory focus theory; upper echelons